Privacy Preservation Model For Data Exposure In Android Smartphone Usage - Abu Bakar, Anizah (2021)
Statistics show there are 6378 million of smartphone users. The usage of mobile applications in smartphones exposes users to privacy risks. This is due to existing works lacking a formalized mathematical model that can quantify both user and system applications risk. There is also no multifaceted data collector tool to monitor user data collection and risk posed by each application. Besides, there is no risk level benchmark that alerts users and distinguishes between acceptable and unacceptable risk levels in smartphone usage. In order to tackle the privacy risk issue, a formalized privacy model called PRiMo is proposed using tree structure and calculus knowledge to quantify the risk in each application, risk posed by each application category, and overall privacy risk faced by the smartphone user.